THE RELATIONSHIP BETWEEN LEARNER AUTONOMY AND MOTIVATION IN EFL SPEAKING CLASS - Dewi, Desi Surlitasari (ELP (Journal of English Language Pedagogy), 2023)
Despite continuous effort to establish an engaging learning environment, there is a lack of motivation among EFL learners in speaking class. Understanding the relationship between autonomy and motivation might provide insights into effective methods of instruction in EFL speaking classes when learners need to strengthen their speaking skills. This study aimed to investigate the relationship between learner autonomy and motivation in higher education, particularly in EFL speaking classes. The research method employed in this correlational study was a questionnaire to assess learner autonomy and motivation. The data were analyzed quantitatively using Pearson product moment and linear regression. The findings indicate a positive correlation between learner autonomy and motivation in EFL speaking classes (r-value = .835; Sig. (2-tailed) .000 < .05). Specifically, learners’ control of cognitive process, independent use of learning resources, learner's control of affective process, and autonomous use of learning skill were significantly correlated with motivation in EFL speaking (r = .731, Sig .001; r = .841, Sig .000; r = .855, Sig .000; r = .753, Sig .000, n=17; Sig .05). Although independent use of technology was not significantly correlated, it had a positive and low correlation towards motivation in EFL speaking (r = .358, Sig .158, n = 17, Sig .05). The five aspects of learner autonomy simultaneously had a strong significant effect on motivation (R2 = .798, p < .001). The findings suggest that educators can design instruction that promote learner autonomy and increase motivation in EFL speaking classes.